FEATURES OF THE PATHOMORPHOLOGICAL DIAGNOSIS OF MICROCRYSTALLINE ARTHROPATHIES IN THE PRACTICE OF SURGICAL MATERIAL EXAMINATION - N. S. Migalkin; T. A. Stupina; A. V. Kaminsky; D. S. Mokhovikov; D. A. Shabalin; B. V. Kamshilov; A. Yu. Kirsanova (Научно-практическая ревматология)
The development of microcrystalline arthritides is most frequently associated with the formation of monosodium urate (MSU) and calcium pyrophosphate (CPP) crystals. Their identification is of crucial importance in recognizing these diseases. Objective: to determine the possibilities of histological techniques in identifying MSU and CPP crystals and to evaluate the effectiveness of the techniques. Subjects and methods. Twenty-four tissue blocks (fragments of the affected areas of the elbow joint, the interphalangeal joint of the index finger, and hip joint) from 7 patients were examined. Paraffin sections were stained with a 0.5% alcohol solution of eosin, as well as with hematoxylin and eosin. Tissue specimens were examined and digitized using an AxioScope.A1 stereo microscope with Zenblue software (Carl Zeiss MicroImaging GmbH, Germany). Results and discussion. When staining the tissue sections with hematoxylin and eosin, microcrystals were not visualized; the major portions of MSU crystals was dissolved during fixation and staining, whereas CPP crystals were masked with hematoxylin as focal basophilic aggregates. The staining technique with an alcohol solution of eosin and short formalin fixation (within 12 hours) made it possible to avoid dissolution of MSU crystals and to visualize both MSU and CPP crystals, and to determine their shape and color. Conclusion. Light microscopy of the tissue sections stained with an alcohol solution of eosin along with short formalin fixation is a reliable method to differentiate MSU and CPP crystals. In patients undergoing endoprosthetic replacement, the significance of this technique for the pathomorphological study of surgical material consists in assessing inflammatory activity and in eliminating a disease, such as microcrystalline arthropathy.